2000
DOI: 10.1017/s1355617700633039
|View full text |Cite
|
Sign up to set email alerts
|

Personality change disorder in children and adolescents following traumatic brain injury

Abstract: The occurrence of personality change due to traumatic brain injury (PC), and its clinical and neuroimaging correlates were investigated. Ninety-four children, ages 5 through 14 at the time of hospitalization following traumatic brain injury (TBI; severe TBI N = 37; mild–moderate TBI N = 57), were assessed. Standardized psychiatric, adaptive functioning, cognitive functioning, family functioning, family psychiatric history, severity of injury, and neuroimaging assessments were conducted. The Neuropsych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 40 publications
8
68
0
Order By: Relevance
“…Personality change accounts for a substantial proportion of NPDs detected in previous studies of psychiatric disorders after TBI. 22,28,29,36 Although emotional lability, irritability, and apathy were endorsed among patients in this study, personality change disorders were not captured and likely lowered the prevalence of NPDs observed in this study. Third, studies have demonstrated that family functioning, socioeconomic status, and preinjury adaptive and intellectual function may contribute to the development of NPDs after pediatric TBI.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Personality change accounts for a substantial proportion of NPDs detected in previous studies of psychiatric disorders after TBI. 22,28,29,36 Although emotional lability, irritability, and apathy were endorsed among patients in this study, personality change disorders were not captured and likely lowered the prevalence of NPDs observed in this study. Third, studies have demonstrated that family functioning, socioeconomic status, and preinjury adaptive and intellectual function may contribute to the development of NPDs after pediatric TBI.…”
Section: Discussionmentioning
confidence: 65%
“…32 Novel psychiatric disorders diagnosed among patients with TBI in these studies were heterogeneous and included depressive disorders, anxiety disorders such as generalized anxiety disorder, panic disorder, posttraumatic stress disorder, and OCD, somatoform disorder, ADHD, and behavioral disorders such as oppositional-defiant disorder and conduct disorder. 4,[21][22][23][26][27][28]30,[34][35][36]49 Among the most common NPDs observed among prospective studies has been personality change resulting from a generalized medical condition, which has been diagnosed in up to 40% of pediatric patients after TBI but was not formally assessed in the present study. 22,36 Clinical variables associated with the development of NPDs after pediatric TBI include history of preinjury psychiatric disorder, family history of psychiatric illness, severity of injury, low socioeconomic status, and preinjury adaptive and intellectual functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EB extravasation was significantly increased in saline treatment (Fig. 2G) ) and began approaching baseline by day 7 (2487 -927 vs. 428 -299 mm 2 ), compared to ML-7-treated mice (Fig. 2H).…”
Section: Eb Extravasationmentioning
confidence: 90%
“…1 Children with TBI are known to suffer a variety of cognitive and behavioral issues, including a loss in developmental milestones and difficulty achieving new ones, change in personality, decline in adaptive functioning, problems in school, and decreased participation in social activities. 2,3 Injured children less than 8 years of age may be especially vulnerable to declines in intelligence and executive functioning, causing difficulty in achieving their full potential and resulting in loss of future revenues. [4][5][6] TBI is a complex injury that leads to a cascade of events that result in compromise of the cognitive and physical functioning of the body.…”
Section: Introductionmentioning
confidence: 99%